ANALYSIS OF FACTORS OF LOW INTEREST IN USING IUD BIRTH CONTROL AT THE SUNGAILIAT HEALTH CENTER 2024 - Rahmawati, Diah; Wahab, Sabda; Fajrianti, Gita (HEARTY, 2025)
Gender and child profile data in 2022 shows that Bangka Belitung Province is ranked 20th with a total of 11.20 in IUD use. The proportion of IUD use in Bangka Regency based on sub-districts consists of Belinyu sub-district 189 acceptors, Sungailiat Health Center 6.48%. The government’s policy on family planning is directed at the use of long-term contraception, but many PUS are less interested in using IUD contraception. The purpose of the study was to determine the factors associated with the low interest of mothers in choosing IUD contraception in the Sungailiat Health Center work area in 2024. This type of research is an analytical survey with a cross-sectional design. The population of this study were all couples of Fertile Age (PUS) who were registered as active KB acceptors in the Sungailiat Health Center work area during the period January - April 2024 with a total of 219. The number of samples was 57 respondents with a purposive sampling technique. The research instrument used in this study was a questionnaire. The results of the study on factors related to low maternal interest in choosing IUD contraceptives at Sungailiat Health Center in 2024, found that knowledge, attitudes, beliefs, health service facilities, and husband’s support were all significantly related to low interest, because the p-value of each was smaller than the α-value of 0.05. With a p-value of 0.00 for knowledge and husband’s support, 0.048 for attitudes, 0.000 for beliefs, and 0.007 for health service facilities, it can be concluded that all of these factors play a role in influencing maternal interest in choosing IUD contraceptives